Novel reversible methionine aminopeptidase-2 (MetAP-2) inhibitors based on purine and related bicyclic templates. Issue 3 (1st February 2017) - Heinrich, Timo; Buchstaller, Hans-Peter; Cezanne, Bertram; Rohdich, Felix; Bomke, Jörg; Friese-Hamim, Manja; Krier, Mireille; Knöchel, Thorsten; Musil, Djordje; Leuthner, Birgitta; Zenke, Frank
Graphical abstract: Both, the purine and the triazolopyrimidine based MetAP-2 inhibitors coordinate the manganese ions in the active site but the 5/6 membered bicyclic ring system is flipped by 180 °C. When binding the latter the imidazole side chain of His339 is pushed out of its conformation with the purine MetAP-2 inhibitor. Abstract: The natural product fumagillin1 and derivatives like TNP-4702 or beloranib3 bind to methionine aminopeptidase 2 (MetAP-2) irreversibly. This enzyme is critical for protein maturation and plays a key role in angiogenesis. In this paper we describe the synthesis, MetAP-2 binding affinity and structural analysis of reversible MetAP-2 inhibitors. Optimization of enzymatic activity of screening hit 10 (IC50 : 1 μM) led to the most potent compound27 (IC50 : 0.038 μM), with a concomitant improvement in LLE from 2.1 to 4.2. Structural analysis of these MetAP-2 inhibitors revealed an unprecedented conformation of the His339 side-chain imidazole ring being co-planar sandwiched between the imidazole of His331 and the aryl-ether moiety, which is bound to the purine scaffold. Systematic alteration and reduction of H-bonding capability of this metal binding moiety induced an unexpected 180° flip for the triazolo[1, 5- a ]pyrimdine bicyclic template.